FUNGSI DOA DI MEDIA SOSIAL: STUDI PRAGMATIK PADA KOMENTAR YOUTUBE - Roby Aji (EPIGRAM (e-journal), 2023)
Communication through digital media has a broad impact on religious life. Posting prayers on an online platform is one of the issues that have arisen. However, no research from a pragmatic perspective has been found that specifically addresses this phenomenon. Therefore, this research was conducted to (1) describe the strategies of speech acts in prayer on YouTube comments, and (2) describe their functions in the social context.  This research is a qualitative-descriptive study. The data were obtained from two videos entitled "Muzammil Hasballah Juz 30 Full" and ”Dosa yang Lebih Besar 1000X dari Zina". This research reveals that generally the prayers uttered contain requests of kindness for the speaker himself and for the others. Even though they are produced in imperative form, the prayers written in the comment section function as a representative and expressive speech act. Therefore, it can be concluded that prayers in the youtube comments  firmly function as a social expression to show religious identity and solidarity of the internet users to the online community.